Challenges in the Management of Community-Acquired Pneumonia in Low- Middle Income Countries. - Muhammad Irfan; Imelda Mateo; Shamsiev Furkat Mukhitdinovich; Kenneth Alberca; Syed Munis Ul Hasan; Jahanzeb Kamal Khan; Javed Iqbal; Jumaa Bwika; Saleem Uz Zaman Adhami (Journal of the Pakistan Medical Association, 2023)
Abstract Despite progress in developing new and powerful medications, Community-acquired Pneumonia (CAP) is still closely linked to significant morbidity and mortality, especially in Low-middle income countries (LMICs). Hence, a group of experts gathered to discuss the main challenges associated with CAP management by the stakeholders (patients, their families/caretakers, Healthcare professionals, and Healthcare policymakers & organizations). During the commencement of the International Respiratory Forum Conference 2022 held in Ho Chi Minh City, Vietnam, a survey was conducted, including 140 pulmonologists from 11 countries. A predesigned structured questionnaire was developed pertaining to challenges faced by each stakeholder for CAP management in LMICs. Physicians were randomly divided into four groups, and only one section of the questionnaire was distributed among the participants to determine their opinion regarding that respective stakeholder’s challenges. Among the patient-related challenges, most physicians believed that self-medication was the most significant reason behind the high mortality rate from CAP as the patients continue to have various troubles in seeking timely diagnosis and treatment. It was found that healthcare expenditure is the most intriguing challenge experienced by families and caretakers of patients with CAP. Moreover, 52% agreed that the diagnosis made by healthcare providers are primarily based on clinical judgment, and Pneumonia Severity Index (PSI) is not commonly used for clinical prediction and patient outcomes. The physicians mostly believed that healthcare policymakers must focus on establishing early diagnostic and treatment strategies to reduce hospitalization rates and costs. Keywords: Community-Acquired Pneumonia, Management, Challenges.